2000
DOI: 10.1111/j.1365-2141.2000.02356.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of congenital leukaemia with an 8;16 translocation

Abstract: Summary. Congenital leukaemia (CL) is a rare disorder that presents with extramedullary infiltrates and a myeloid phenotype. CL can progress rapidly without adequate treatment, but, paradoxically, may also remit spontaneously. Because of the significant toxicity involved in delivering chemotherapy to newborns, it is important to identify those newborns who may not require treatment. We describe an infant who presented at 1 week of age with congenital myeloid leukaemia. Cytogenetic analysis revealed a t(8;16)(q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…43 A t(8;16)(q11;p13), probably involving CREBBP, has also been reported in a congenital AML-M4 with spontaneous regression. 44 In contrast to these three regressive cases, the prognosis of AML with t(8;16) is overall poor. Indeed, although patients of our series were often old and therapies were different, our data confirm the poor prognosis of MYST3-linked AML.…”
Section: Prognostic Featuresmentioning
confidence: 99%
“…43 A t(8;16)(q11;p13), probably involving CREBBP, has also been reported in a congenital AML-M4 with spontaneous regression. 44 In contrast to these three regressive cases, the prognosis of AML with t(8;16) is overall poor. Indeed, although patients of our series were often old and therapies were different, our data confirm the poor prognosis of MYST3-linked AML.…”
Section: Prognostic Featuresmentioning
confidence: 99%
“…In contrast to childhood leukemia, neonate and infant leukemia is classified more frequently as myeloid than lymphoblastic leukemia (9:1) [3]. Although the prognosis of CL is poor, spontaneous remissions have been reported [4,5].Lineage switches of the leukemic cell clones from lymphoid to myeloid and vice versa have been reported infrequently. Our experience with such a case is of interest.…”
mentioning
confidence: 99%
“…The incidence could be higher, because it might take 2 to 3 months for the spontaneous remission to occur, and cytotoxic treatment was often administered early in reported cases of congenital or neonatal leukemia with t(8;16) translocation. Weintraub et al [17] also reported a neonate who presented with purple-blue cutaneous nodules and acute myelomonocytic leukemia that spontaneously regressed after 5 months. Cytogenetic analysis showed t(8;16)(q11;p13) with a different breakpoint in chromosome 8, suggesting rearrangement of CREBBP might be the more important genetic alteration in this unusual form of self-limiting leukemia in neonates.…”
Section: Discussionmentioning
confidence: 94%